Boosting the quality of life through additional general allocation funds for village infrastructure development - Khusaini Khusaini; Asep Ferry Bastian; Hudaya Latuconsina; Rommy Pratama (International Journal of Public Health Science (IJPHS), 2023)
Improving the quality of life of the community as one of the key indicators of development success is a must since it has an impact on the wellbeing of the community. This study aims to measure quality of life and analyze the effect of additional general allocation funds for village infrastructure development, education, and control variables on the quality of life of the community who lived in Tangerang. The researchers employed a sample size of 368 people. Using a cross-sectional survey approach, valid, and reliable questionnaires were distributed. The results of the multiple regression analysis showed that the general allocation funds for the village infrastructure development were proven to have a significant effect on improving the quality of life of the community. The education level variable did not have a significant effect on improving the quality of life, but it had a significant effect on the psychological health domain of quality of life. In addition to the provision and maintenance of health services, it is necessary for the government to include the construction of infiltration wells, community-based domestic wastewater management networks, light fire extinguishers, and portable fire pumps as development priorities.